Relationship Between Financial Support and Retention of Economically Disadvantaged Students in an Undergraduate Baccalaureate Nursing Program - (:unkn) unknown (My University, 2016)
Retention in baccalaureate nursing programs has been a concern for administrators and educators for decades. The non-traditional students of the past have become the traditional students of the present and as such lead complex lives. The emerging group of students that requires more attention in nursing education research is the economically disadvantaged students. Economically disadvantaged students typically come to college less prepared for the rigors of higher education and are at-risk for leaving post-secondary education. Retention of economically disadvantaged students can potentially increase the diversity of the nursing workforce since many economically disadvantaged students also come from ethnically diverse background. Federally funded grant programs such as the HRSA Scholarships for Disadvantaged Students can impact the retention of economically disadvantaged students in baccalaureate nursing programs by providing much needed tuition assistance as well as monies that could also be used for child care services, rent, and basic living expenses. The purpose of this study was to evaluate selected outcomes of grant support from the Scholarships for Disadvantaged Students (SDS) program on students in a baccalaureate nursing program in one Midwestern institution. The research questions for this study were: Research Question 1: After controlling for differences in demographic characteristics, is receipt of SDS financial support associated with (a) a reduction in hours worked per week, (b) an increase in study hours per week, (c) higher nursing GPA and overall GPA, and (d) higher rates of retention in and progression through to program completion in a baccalaureate nursing program? Research Question 2: After accounting for differences in demographic characteristics, to what extent and in what manner is retention and progression in a baccalaureate nursing program predicted by SDS financial support, hours worked per week, study hours per week, nursing GPA and overall GPA? This study was a quasi-experimental design utilizing secondary analysis of existing data from available university databases as well as data obtained from a questionnaire developed by the student principal investigator. The sample was 351 subjects in three groups of undergraduate pre-licensure students (SDS, pre-SDS, non-SDS) from the traditional undergraduate nursing program who met the eligibility requirements outlined by HRSA for Scholarships for Disadvantaged Students. Data analysis included descriptive and correlational statistics as well as Chi-squared and ANOVA. A significant difference among groups was found for the variable explaining the relationship between study and work hours (study to work hours). Students receiving SDS financial support on average studied nearly five more hours per week than they worked; the comparison group (pre-SDS) on average worked two more hours per week than they studied. In addition, students receiving SDS financial support had higher overall GPA and higher final nursing GPA than the other two groups. Students receiving SDS financial support had 96.3% on time program completion. Logistic regression was conducted using a combination of variables. The most parsimonious predictor of on time graduation included only the variables SDS grant status and initial GPA. Students receiving the SDS grant were 10 times more likely to graduate on time than those who did not receive the grant (CI 95%, 3.03-33.76). This study provides evidence that financial support in the form of grant funding can influence retention and program completion for economically disadvantaged undergraduate nursing students by impacting the students’ ability to study more hours per week than they work. This may be the first study to look at the impact of SDS federal grant funding and undergraduate nursing program completion. The student receiving the grant funding all progressed to the next semester and 96% completed the nursing program in the prescribed five semesters.
Keywords: Baccalaureate; Economically Disadvantaged; Nursing Education; Retention